Assessment of Tandem Measurements of pH and Total Gut Transit Time in Healthy Volunteers - Mikolajczyk, Adam E (Clin Transl Gastroenterol, 2015)
OBJECTIVES: The variation of luminal pH and transit time in an individual is unknown, yet is necessary to interpret single measurements. This study aimed to assess the intrasubject variability of gut pH and transit time in healthy volunteers using SmartPill devices (Covidien, Minneapolis, MN). METHODS: Each subject (n=10) ingested two SmartPill devices separated by 24 h. Mean pH values were calculated for 30 min after gastric emptying (AGE), before the ileocecal (BIC) valve, after the ileocecal (AIC) valve, and before body exit (BBE). Intrasubject variability was determined by comparing mean values from both ingestions for an individual subject using standard deviations, 95% limits of agreement, and Bland-Altman plots. RESULTS: Tandem device ingestion occurred without complication. The median (full range) intrasubject standard deviations for pH were 0.02 (0.0002–0.2048) for AGE, 0.06 (0.0002–0.3445) for BIC, 0.14 (0.0018–0.3042) for AIC, and 0.08 (0.0098–0.5202) for BBE. There was a significant change in pH for AIC (mean difference: −0.45±0.31, P=0.0015) observed across all subjects. The mean coefficients of variation for transit time were 12.0±7.4% and 25.8±15.8% for small and large bowels, respectively (P=0.01). CONCLUSIONS: This study demonstrates the safety and feasibility of tandem gut transit and pH assessments using the SmartPill device. In healthy individuals and over 24 h, the gut pH profile does not markedly fluctuate in a given region with more variation seen in the colon compared with the small bowel, which has important implications for future physiology and drug delivery studies.